Development of an Ethnoscience-Based E-Module with the PBL Model to Improve Problem-Solving and Critical Thinking Skills: A Literature Review - Yulia Hasan; Susilawati Susilawati; Gunawan Gunawan; Yayuk Andayani (Current Educational Review, 2025)
Problem-solving and critical thinking skills are important skills that students must have in learning physics. Problem-solving and critical thinking skills can be facilitated through the use of ethnoscience- based e-modules with the PBL model. This study aims to identify and analyze research trends using ethnoscience -based e-modules with the PBL model to improve problem-solving and critical thinking skills in physics learning. This research method is descriptive and analytical. The data used in this study were obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. The research procedure used the PRISMA guidelines. The data identified and analyzed were the types of publications, sources of publications, and research titles on the PBL model to improve problem-solving and critical thinking skills in physics learning that were widely cited. The data analysis method used bibliometric analysis assisted by VOS viewer software. The results showed that research trends on this topic had increased significantly from 2015 to 2024. This indicates a high interest in innovative approaches that combine local cultural aspects (ethnoscience) with problem-based learning strategies